Amyand's Hernia in Children: Intraoperative Finding, A Rare Case Report From dr. Azhar Zahir Naval Hospital, Manokwari, West Papua - Trisha Fabiola Novena; Oswaldus Sixtus Nahak; Ridho Sinaga (CV. Inara, 2026)
Amyand’s hernia is a rare type of inguinal hernia in which the vermiform appendix is found within the hernia sac. Preoperative diagnosis is challenging because its clinical presentation often resembles an incarcerated inguinal hernia, making intraoperative diagnosis common. A 1-year-old boy presented with an irreducible right inguinal swelling that had been present since infancy and became non-reducible one week before admission. Physical examination revealed an irreducible right inguinal mass, while laboratory findings were unremarkable. No preoperative imaging was performed, and the patient underwent emergency herniotomy. Intraoperative exploration revealed the cecum and an edematous, hyperemic vermiform appendix within the hernia sac, consistent with Amyand’s hernia complicated by acute appendicitis. Appendectomy followed by primary hernia repair without mesh was performed. The postoperative course was uneventful, and the patient was discharged on the third postoperative day without complications. Amyand’s hernia remains a rare and difficult preoperative diagnosis in pediatric patients. Intraoperative recognition is essential for appropriate surgical management. This case supports the use of appendectomy and primary hernia repair without mesh for Type 2 Amyand’s hernia, resulting in an excellent postoperative outcome.